Aperiodically intermittent synchronization of Markovian jump stochastic complex networks with time-varying delays. Issue 13 (2nd October 2020) - Guo, Beibei; Xiao, Yu; Zhang, Chiping
ABSTRACT: In this paper, p th-moment exponential synchronization for Markovian jump stochastic complex networks with time-varying delays (MJSCNTVDs) is studied via aperiodically intermittent control. By combining graph theory and M -matrix theory, some novel synchronization criteria are derived, which comprise two forms: (1) Lyapunov-type criteria and (2) coefficient-type criteria. As its applications, the obtained synchronization results are applied to explore p th-moment exponential synchronization of stochastic coupled oscillators with time-varying delays and Markovian jump. The primary advantages of these obtained results over some recent and similar works are that the differentiability or continuity of the delay function is not required and that the restriction between control width and delay is removed. Two numerical examples are provided to examine the effectiveness and potential of the theoretic results obtained.